2020
DOI: 10.5455/msm.2020.32.117-122
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Breastfeeding and Obesity in Preschool Children

Abstract: Introduction: Childhood obesity is a significant problem nowadays, with breastfeeding being one of many factors responsible for this issue. Breastfeeding as a natural way of feeding infants has many benefits for the child, the mother, and society. Aim: The present study aimed to investigate the association between overweight children in preschool age and breastfeeding duration. Methods: The current study included 674 preschool children aged 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…After excluding duplicates, 17,871 titles were examined, and after excluding those studies that were clearly irrelevant, 269 abstracts were reviewed, and 58 19–76 new studies were identified in the update of the systematic review (Figure 1). The meta‐analysis comprised 169 estimates on the association of breastfeeding with overweight or obesity, drawn from 159 studies including 58 that were published since our previous review (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…After excluding duplicates, 17,871 titles were examined, and after excluding those studies that were clearly irrelevant, 269 abstracts were reviewed, and 58 19–76 new studies were identified in the update of the systematic review (Figure 1). The meta‐analysis comprised 169 estimates on the association of breastfeeding with overweight or obesity, drawn from 159 studies including 58 that were published since our previous review (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies in humans investigated the impact of breastfeeding versus formula-feeding nutrition. Overall, studies indicate that breastfeeding exerts a protective role in the development of overweight and obesity during childhood [ 31 , 32 , 33 ]. Despite studies being affected by confounding factors, such as the observational study design, the time, duration, exclusivity of breastfeeding, or the study location, most have demonstrated the positive effect of breastfeeding, which is more evident related to the duration of breastfeeding for more than 4–6 months and its exclusivity [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Breastfeeding is known to have protective effects on childhood obesity. Previous studies have shown that breastfed children are more likely to have normal BMI compared to children who were breastfed less than 6 months (Pattison et al, 2019;Palaska et al, 2020). Additionally, increased in breastfeeding duration reduced the probability of being obese at 2 years old (Modrek, 2015).…”
Section: Discussionmentioning
confidence: 99%